2008
DOI: 10.1159/000141641
|View full text |Cite
|
Sign up to set email alerts
|

Post-Treatment Outcomes of Buprenorphine Detoxification in Community Settings: A Systematic Review

Abstract: A systematic review was undertaken to examine studies of buprenorphine detoxification that has included post-treatment outcomes as well as more immediate aspects of progress. Studies were required to report details of buprenorphine withdrawal regime and post-treatment outcomes including abstinence rates. Only five studies met these criteria, with buprenorphine regimes lasting 3 days to several weeks, and with variable follow-up. Detoxification completion rates were 65–100%, but relatively few treatment complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The association between perceived risk of relapse and intended BMT duration found in this study and others (Winstock et al, 2011) may be particularly important given that relapse rates after BMT discontinuation are very high (Bailey et al, 2013; Bentzley et al, 2014; Dunn et al, 2011; Horspool et al, 2008; Kornør et al, 2007), and some patients may underestimate their risk of relapse with treatment discontinuation. It is known that individuals with high perceived risk of relapse have greater interest in maintenance medications after detoxification (Bailey et al, 2013).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The association between perceived risk of relapse and intended BMT duration found in this study and others (Winstock et al, 2011) may be particularly important given that relapse rates after BMT discontinuation are very high (Bailey et al, 2013; Bentzley et al, 2014; Dunn et al, 2011; Horspool et al, 2008; Kornør et al, 2007), and some patients may underestimate their risk of relapse with treatment discontinuation. It is known that individuals with high perceived risk of relapse have greater interest in maintenance medications after detoxification (Bailey et al, 2013).…”
Section: Discussionmentioning
confidence: 51%
“…Unfortunately, although outcomes improve with longer OMT duration (Hubbard, Craddock, & Anderson, 2003; Zhang, Friedmann, & Gerstein, 2003), the benefits of OMT do not frequently endure after treatment cessation. Rates of relapse to illicit opioid use (Bentzley, Barth, Back, & Book, 2014; Dunn, Sigmon, Strain, Heil, & Higgins, 2011; Horspool, Seivewright, Armitage, & Mathers, 2008; Kornør, Waal, & Sandvik, 2007) and mortality (Clausen et al, 2008; Degenhardt et al, 2011) both increase when patients are no longer enrolled in OMT.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this less severe withdrawal syndrome, the approval of buprenorphine was heralded by enthusiasm for improved outcomes following detoxification (National Consensus Development Panel on Effective Medical Treatment of Opiate Addiction, 1998) apropos of the high relapse rates known to accompany discontinuation of methadone OMT (Amato et al, 2013). Unfortunately, buprenorphine detoxification has not lead to increased rates of abstinence following withdrawal (Dunn et al, 2011; Horspool, Seivewright, Armitage, & Mathers, 2008), and as such, the practice of BMT discontinuation may be perpetuated by the provider expectation that abstinence is likely to follow (Newman, 2009). Furthermore, some providers may feel that abiding by program rules is necessary for BMT success to the extent that BMT is discontinued for rule infractions; however, patients often find benefit in remaining in programs despite failure to achieve program-imposed criteria (Mitchell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although patient satisfaction with buprenorphine treatment is high (Barry et al, 2007; Ling, Hillhouse, Ang, Jenkins, & Fahey, 2013), many patients ask to discontinue BMT after several months of treatment (Kleber, 2007), a preference that could be driven in part by perceived low probability of relapse (Bailey, Herman, & Stein, 2013). Hence, it is essential that both physician and patient harbor realistic, evidence-based expectations of outcomes following discontinuation of BMT; however, current systematic reviews of BMT discontinuation have focused on its use in detoxification protocols (Dunn et al, 2011; Horspool et al, 2008) and no current reports could be found that link perspectives of patients or providers with outcomes. Here we bridge patient and provider perspectives of BMT with rates of abstinence following discontinuation of BMT by systematically reviewing patient and provider perspectives that may lead to BMT discontinuation after a period of stable BMT and the outcomes that follow.…”
Section: Introductionmentioning
confidence: 99%
“…11,13 Buprenorphine, the second well-established opiate maintenance treatment, was suggested to be associated with less sedation and less impairment of cognitive performance. 14 However, neither buprenorphine nor methadone treatment impaired task performance on a multi-source interference task, combining attention and inhibitory capacity tasks. 15 In addition, a dose effect study of buprenorphine demonstrated impairment of complex cognitive functioning in participants who received high doses of buprenorphine (32 mg).…”
mentioning
confidence: 99%